2017
DOI: 10.1186/s12936-017-1840-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous determination of blood glucose in children admitted with malaria in a rural hospital in Mozambique

Abstract: BackgroundHypoglycaemia is a frequent complication among admitted children, particularly in malaria-endemic areas. This study aimed to estimate the occurrence of hypoglycaemia not only upon admission but throughout the first 72 h of hospitalization in children admitted with malaria.MethodsA simple pilot study to continuously monitor glycaemia in children aged 0–10 years, admitted with malaria in a rural hospital was conducted in Southern Mozambique by inserting continuous glucose monitors (CGMs) in subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 39 publications
2
21
2
Order By: Relevance
“…In the present study, no case of relapse of severe hypoglycemia was observed after admission, unlike some authors who reported a relatively large number of cases [13] [28] [29]. It is difficult to make a relevant analysis of our results, because of the low number of cases of severe hypoglycemia.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…In the present study, no case of relapse of severe hypoglycemia was observed after admission, unlike some authors who reported a relatively large number of cases [13] [28] [29]. It is difficult to make a relevant analysis of our results, because of the low number of cases of severe hypoglycemia.…”
Section: Discussioncontrasting
confidence: 52%
“…However, Madrid et al in Mozambique found a higher incidence of hypoglycemia than hyperglycemia on admission and the same frequency of both abnormalities after admission [13]. This difference is related to the fact that the Madrid study population was composed of children with uncomplicated and severe malaria, and the definition of hyperglycemia (blood glucose ≥ 11.0 mmol/L) [13] was different from the one used in our study (blood glucose ≥ 8.3 mmol/L).…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…The exact patterns of glycemia in SAM remain largely unknown ( 37 ), and in high-resource contexts it is reported that glucose variability is associated with increased mortality in sick children ( 36 ). A way of investigating the patterns of blood glucose concentrations and identifying any episodes of asymptomatic hypoglycemia is using a continuous glucose monitoring system.These have been used in very low birth weight infants ( 38 ) and children with malaria where over 15% of children with hypoglycemia were asymptomatic ( 39 ). Continuous glucose monitoring systems have not been used in children with SAM before, and could provide valuable insights into the occurrence, risk factors, and clinical impact of dysglycemia in these children.…”
Section: Discussionmentioning
confidence: 99%